ประสิทธิผลของกลยุทธ์การตลาดที่มีผลต่อการส่งเสริมคุณค่าการท่องเที่ยว เชิงพุทธศาสนาพระอารามหลวงในกรุงเทพมหานคร - มะสันเทียะ, พระมหาสุริยา (Journal of Graduate School of Commerce-Burapha Review, 2016)
การวิจัยครั้งนี้ มีวัตถุประสงค์ 1) เพื่อสำรวจปัจจัยส่วนบุคคลของนักท่องเที่ยวชาวไทยและชาวต่างชาติ 2) เพื่อศึกษา กิจกรรมการตลาดการท่องเที่ยวเชิงพุทธศาสนาในปัจจุบัน 3) เพื่อศึกษากลยุทธ์การตลาดการท่องเที่ยวเชิงพุทธศาสนา พระอารามหลวงในกรุงเทพมหานคร 4) เพื่อวิเคราะห์ความสัมพันธ์เชิงสาเหตุระหว่างปัจจัยส่วนบุคคลของนักท่องเที่ยว กิจกรรมการตลาดการท่องเที่ยวเชิงพุทธศาสนา ที่ส่งผลต่อกลยุทธ์การตลาดการท่องเที่ยวเชิงพุทธศาสนา และนำไปสู่ การส่งเสริมคุณค่าการท่องเที่ยวเชิงพุทธศาสนา การวิจัยครั้งนี้ เป็นการวิจัยแบบผสมผสานโดยแบ่งได้เป็น 2 ส่วน คือ ส่วนที่ 1 การวิจัยเชิงปริมาณ โดยเก็บข้อมูล จากกลุ่มตัวอย่างนักท่องเที่ยว จำนวน 900 คน โดยใช้แบบสอบถามเป็นเครื่องมือในการเก็บข้อมูล และส่วนที่ 2 การวิจัย เชิงคุณภาพ โดยเก็บข้อมูลกลุ่มตัวอย่างจากบุคคลที่มีส่วนเกี่ยวข้องกับการท่องเที่ยวเชิงพุทธศาสนา จำนวน 18 คน โดยใช้วิธีสัมภาษณ์เชิงลึก วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา อนุมาน และการวิเคราะห์โมเดลสมการโครงสร้างใช้ โปรแกรมคอมพิวเตอร์ ผลการวิจัยพบว่า ปัจจัยส่วนบุคคลของนักท่องเที่ยวมีความสัมพันธ์เชิงบวกโดยตรงต่อกิจกรรมการตลาด การท่องเที่ยวเชิงพุทธศาสนา และปัจจัยส่วนบุคคลของนักท่องเที่ยวมีความสัมพันธ์เชิงบวกโดยตรงและทางอ้อม กับกลยุทธ์ การตลาดการท่องเที่ยวเชิงพุทธศาสนา โดยผ่านกิจกรรมการตลาดการท่องเที่ยวเชิงพุทธศาสนา ส่วนกิจกรรมการตลาด การท่องเที่ยวเชิงพุทธศาสนา มีความสัมพันธ์เชิงบวกโดยตรงไปยังกลยุทธ์การตลาดการท่องเที่ยวเชิงพุทธศาสนาและ กิจกรรมการตลาดการท่องเที่ยวเชิงพุทธศาสนา มีความสัมพันธ์เชิงบวกทางอ้อมกับประสิทธิผลที่ได้จากกลยุทธ์การตลาด ในการส่งเสริมคุณค่าการท่องเที่ยวเชิงพุทธศาสนา โดยผ่านกลยุทธ์การตลาดการท่องเที่ยวเชิงพุทธศาสนา ส่วนกลยุทธ์ การตลาดการท่องเที่ยวเชิงพุทธศาสนา มีความสัมพันธ์เชิงบวกโดยตรงไปยังประสิทธิผลที่ได้ จากกลยุทธ์การตลาด ในการส่งเสริมคุณค่าการท่องเที่ยวเชิงพุทธศาสนาและโมเดลความสัมพันธ์เชิงสาเหตุที่พัฒนาขึ้น จากการวิจัยมีความเหมาะสม เนื่องจากมีความสอดคล้องกับข้อมูลเชิงประจักษ์ และแต่ละองค์ประกอบของโมเดลมีความเที่ยงตรง มีความสามารถ ในการพยากรณ์ได้ระดับดีและเป็นที่ยอมรับได้ THE EFFECT OF MARKETING STRATEGIES AFFECTING THE ENHANCEMENT OF BUDDHIST TOURISM IN BANGKOK Pramahasuriya Masunthia Faculty of Business Administration Siam University Bangkok 10160, Thailand The study aimed 1) to survey the personal factor of the buddhist tourists in Royal Monasteries of Bangkok 2) to study the current buddhist marketing activities 3) to study the marketing strategies of buddhist tourism in Royal Monasteries of Bangkok 4) to analyze the causal relationship between tourists’ personal factor and the current marketing activities of Buddhist tourism, resulting in the marketing strategies of Buddhist tourism and leading to the enhancement of Buddhist tourism. This research is a mixed research, as divided into 2 parts. Namely, the 1st part was a quantitative research, the sample groups of which were 900 tourists by using the sets of questionnaire as tools for data collection; the 2nd part was a qualitative research, the sample groups of which were 18 representatives in the work units in relation to the Buddhist tourism. This study was based upon a documentary study and in-depth interview from the person in association with the tourist circles of Thailand. The data were analyzed by descriptive statistics and inferential statistics and the structural equation modeling was analyzed by using computer program. The results found that the personal factor of the tourists had positive and negative relationships as directly to the marketing activities of buddhist tourism and the personal factor of the tourists had positive and negative relationships as directly and indirectly to the marketing strategies of buddhist tourism via the marketing activities of buddhist tourism; the marketing activities of buddhist tourism had positive relationship as directly to the marketing strategies of buddhist tourism and the marketing activities of the buddhist tourism had positive relationship as indirectly to the effectiveness derived from the marketing strategies in enhancement of buddhist tourism via the marketing strategies of Buddhist tourism; and the marketing strategies of buddhist tourism had positive relationship as directly to the effectiveness derived from the marketing strategies in enhancement of buddhist tourism.The causal model developed is appropriate because they are consistent with the empirical data. Elements of the model are accurate (Validity) and have the ability to predict and are an acceptable level.